MODIFIKASI GARAP GENDHING OREK-OREK GAYA REMBANG - Prayugalihingtyas Dwi Hapsari; Muhammad Nur Salim; Ananto Sabdo Aji (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2025)
The research entitled "Modification garap of Gendhing Orek-Orek gaya Rembangan" aims to analyse the modification that occur in Gendhing Orek-Orek gaya Rembangan, as well as describe the factors that influence the modification. Analyzing the modification that occur in Gendhing Orek-Orek gaya Rembangan uses the theory offered by Supandi and Rahayu Supanggah. To describe the modification factors using the theory offered by Shils and Rahayu Supanggah. The metode used in the research is a qualitative research method with the stages carried out, namely data collection and data analysis. The modification that occurs in Gendhing Orek-Orek gaya Rembangan is done by a process that produces a new Gendhing Orek-Orek by changing the structure and performance. The structure has the addition of suwuk gropak and buka celuk. Garap experienced changes and additions to the materi garap, sarana garap, and prabot garap. The occurrence of modifications is caused by factors such as the awareness of the performer, the quality of the individual, and other driving factors such as garap considerations, public tastes, and revitalization of the arts.